Comparative treatment effectiveness of direct acting antiviral regimens for hepatitis C: Data from the Veterans administration. Issue 6 (30th May 2017) - Fox, D Steven; McGinnis, Justin J; Tonnu‐Mihara, Ivy Q; McCombs, Jeffrey S
Abstract: Background and Aims: Data addressing real world effectiveness of direct acting antiviral agents in hepatitis C infected patients are now emerging. This study compared the sustained virologic response rates achieved 12 weeks post‐treatment in patients treated with three such agents by the Veterans Health Administration. Methods: A retrospective cohort study was conducted using patients who terminated treatment by July 1, 2015. Data were retrieved from the Veterans Health Administration electronic medical records system. Patients were included if sufficient viral load laboratory data were available to determine sustained virologic response. Applying an intention to treat approach and logistic regression analysis, the sustained virologic response rates achieved were compared across drug regimens. Results: A total of 11 464 patients met study selection criteria. Without controlling for other risk factors, sustained virologic response at least 12 weeks post treatment was achieved in 92% of ledipasvir/ sofosbuvir, 86% of ombitasvir/paritaprevir/ritonavir/dasabuvir, and 83% of simeprevir/sofosbuvir patients. After adjusting for patient characteristics, simeprevir/sofosbuvir (93.3%) and ledipasvir/sofosbuvir (96.2%) patients were statistically more likely than ombitasvir/paritaprevir/ritonavir/dasabuvir (91.8%) patients to demonstrate sustained virologic response. Human immunodeficiency virus, hepatitis B infection, diabetes, obesity, previous treatment history and augmentation therapy using ribavirin did not impact sustained virologic response rates. Sustained virologic response rates were lower for patients under age 65, with cirrhosis, decompensated cirrhosis, hepatocellular carcinoma, indications of fibrosis, or a non‐genotype 1 infection. Women and Caucasian patients were more likely to achieve a sustained virologic response. Conclusions: All three direct acting antiviral regimens appear highly effective in achieving sustained virologic response.